The Influence of Conflict and Work Stress on Employee Performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency - A. Nur Aviva Ismar; M. Hidayat; A. Muhiddin Daweng (CV. AFDIFAL MAJU BERKAH, 2024)
Nur Aviva Ismar, 2024,